(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The composite materials are replacing the traditional materials, because of its superior properties such as high tensile strength, low thermal expansion, high strength to weight ratio. The developments of new materials are on the anvil and are growing day by day. Fiber composites such as Calotropis gigantea– GFRP became more attractive due to their better properties which are using for Aircraft applications. In this connection we are fabricating Calotropis gigantea– GFRPcomposite with two different resins, vinyl resin and polypropylene resin. After fabricated Calotropis gigantea– Gyrocompasses send for mechanical tests like Tensile, flexural, and Impact for experimental study.